Normative convergence between global health security and universal health coverage: a qualitative analysis of international health negotiations in the wake of COVID-19 - Arush Lal; Clare Wenham; Justin Parkhurst (Globalization and Health)
Abstract Background The UN Sustainable Development Goals (SDGs) and WHO Thirteenth General Programme of Work underscored the importance of mitigating health emergencies while ensuring accessible and affordable health services. Central to these efforts are global health security (GHS) and universal health coverage (UHC), which act both as standalone goals and as cross-cutting approaches to health policy and practice. While GHS and UHC each operate as distinct norms, global health stakeholders increasingly advocate for advancing them synergistically to address interconnected health challenges amid limited resources. However, the current extent of alignment between GHS and UHC remains unclear, especially post-COVID-19. This qualitative study assesses normative convergence between GHS and UHC by tracing their development through iterative draft texts across two major international health negotiations – specifically examining how UHC norms are expressed in the WHO Pandemic Agreement, and how GHS norms are expressed in the 2023 UNGA Political Declaration on Universal Health Coverage. Results UHC was promoted in the WHO Pandemic Agreement through three closely-associated discourse themes (rights-based narratives, equity frames, focus on social determinants of health) and three closely-associated core functions (accessible and affordable health commodities, prioritizing vulnerable populations, primary health care approach). Meanwhile, GHS was reciprocally promoted in the 2023 UHC Political Declaration through three related discourse themes (existential threat narratives, resilience frames, focus on infectious diseases) and three related core functions (outbreak preparedness, health emergency response, One Health approach). Conclusions The findings indicate that the COVID-19 pandemic created a policy window uniquely-positioned to accelerate normative convergence between GHS and UHC. Both international agreements advanced convergence by demonstrating increased complementarity and interdependency between the two norms through the co-promotion of their underlying features. However, negotiators agreed to political and operational trade-offs which made it difficult to sustain progress. This study provides a nuanced account of how global health norms evolve through integration in complex policy environments – finding that normative convergence may not always be explicit, but rather implicit through incremental linkages in their underlying discourse and core functions. This research contributes to pragmatic efforts by global health actors seeking consensus amidst an era of polycrisis, and highlights the importance of navigating geopolitics and overcoming path dependencies. It also deepens scholarly understanding on how ‘hybrid norms’ develop through the dynamic process of normative convergence via diplomacy.